Hubungan Kebutuhan Pelayanan Keluarga Berencana pada Remaja Belum Kawin dengan Niat Menggunakan Kontrasepsi di Masa Dewasa (Analisis SDKI 2017) - Adella, Tiara; Damayanti, Rita; Makful, Martya Rahmaniati (UI Scholars Hub, 2021)
Background. Indonesia is the country with the most population in Southeast Asia. In anticipating a Population Growth Rate problem, the government is preparing a family planning program with youth as one of the targets. Objective. This study aimed to determine the relationship between the need for family planning services in unmarried adolescents and the intention to use contraception in adulthood. Method. The study is quantitative analytic with a cross-sectional approach. The questionnaire used by Adolescent Men (RP) and Women of Fertile Age (WUS). The population in this study were all unmarried adolescents in Indonesia, with sample amount 18,464 respondents. Results. 82.6% of adolescents intend to use contraception in the future. Chi-square test results show a relationship between the need for family planning services for unmarried adolescents with the intention to use contraception in adulthood. The result of the multivariate analysis shows a relationship between the need for family planning services for unmarried adolescents with the intention to use contraception in adulthood after being controlled for confounding variables. Conclusion: Unmarried male adolescents who do not need family planning services, are exposed to mass media, have knowledge of